2017
DOI: 10.1016/j.neuropsychologia.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Brain-based individual difference measures of reading skill in deaf and hearing adults

Abstract: Most deaf children and adults struggle to read, but some deaf individuals do become highly proficient readers. There is disagreement about the specific causes of reading difficulty in the deaf population, and consequently, disagreement about the effectiveness of different strategies for teaching reading to deaf children. Much of the disagreement surrounds the question of whether deaf children read in similar or different ways as hearing children. In this study, we begin to answer this question by using real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…From this standpoint, our findings are comparable with those of another recent study (Mehravari, Emmorey, Prat, Klarman, & Osterhout, ), which found that reading comprehension scores were better predicted by N400 responses to semantic anomalies in deaf subjects, but were more associated to P600 responses to syntax violations in hearing readers. This was interpreted as evidence for different reliance on lexical‐semantic and grammatical processes for comprehension between groups.…”
Section: Discussionsupporting
confidence: 90%
“…From this standpoint, our findings are comparable with those of another recent study (Mehravari, Emmorey, Prat, Klarman, & Osterhout, ), which found that reading comprehension scores were better predicted by N400 responses to semantic anomalies in deaf subjects, but were more associated to P600 responses to syntax violations in hearing readers. This was interpreted as evidence for different reliance on lexical‐semantic and grammatical processes for comprehension between groups.…”
Section: Discussionsupporting
confidence: 90%
“…This pattern of correlations indicates that in adult deaf readers, better metaphonological abilities and a higher reading ability are related to late, lexical effects. The correlation between the size of the N400 on the later window and reading ability measures is also consistent with results from a recent ERP study (Mehravari, Emmorey, Prat, Klarman, & Osterhout, 2017) that found a correlation in deaf readers between the size of the N400 for semantically anomalous sentence endings and their standardized reading scores. Mehravari et al (2017) conclude that, unlike hearing readers, deaf readers rely primarily in semantic information, using the "good-enough" approach to reading (Ferreira et al, 2002).…”
Section: Relationships Between Phonological Priming and Reading-relatsupporting
confidence: 89%
“…Another contributing factor to the lack of correlation between reading comprehension scores and the rest of the measures in the hearing but not in the deaf participants might be their use of other grammatical information, such as syntax, to complete this task. Mehravari et al, (2017) found that the size of the P600…”
Section: Relationships Between Phonological Priming and Reading-relatmentioning
confidence: 99%
“…These results indicate that similar neural processes are involved in semantic processing for deaf and hearing readers at the sentence level. However, Mehravari et al (2017) found that only the The neurobiology of reading 21 hearing readers exhibited a significant P600 to syntactic violations. Importantly, this pattern also held for the subgroup of skilled deaf readers who were matched with the hearing participants on reading ability.…”
Section: <1> Sentence Readingmentioning
confidence: 91%
“…More recently, Mehravari et al (2017) investigated ERP responses to semantic violations (e.g., The huge house still listen to my aunt) which as noted above generate a large N400, and to syntactic violations (e.g., The huge house still belong to my aunt) which generate a P600, a positive-going wave that peaks about 600 ms after the grammatical error. The deaf participants in this study were all prelingually and profoundly deaf and varied in their age of exposure and use of a signed language, although the majority of participants were signers.…”
Section: <1> Sentence Readingmentioning
confidence: 99%